Gastronomy Tourism Contribution To The Development Of Halal Tourism In Aceh - Atika; Ihdi Aini; Reni Ria Armayani Hasibuan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the contribution of gastronomic tourism to the development of halal tourism in Aceh by highlighting three main indicators, namely gastronomic products, food culture, and consumption habits. This study uses a descriptive quantitative method. The sampling technique used in this study is non-probability sampling, where 50 local and foreign tourists visiting Aceh City were selected as respondents. The data were analyzed using SPSS version 21 with a T-test to determine the effect of each variable on the development of halal tourism. The results showed that the halal product variable had a positive and significant effect on the development of halal tourism with a T-test value of 4.608 and a significance level of 0.00 (<0.10). This shows that halal gastronomic products play an important role in increasing the attractiveness of halal tourism. In addition, the tourist consumption trend variable also has a significant effect on the development of halal tourism with a T-test value of 4.139 and a significance level of 0.00. Meanwhile, the tourist experience variable has a T-test value of 4.834, which shows that tourists' positive experiences with halal services contribute to the growth of halal tourism in Aceh. Simultaneously, the three variables have been proven to have a significant impact on the development of halal tourism. Thus, strengthening the quality of halal products, understanding tourist consumption trends, and improving tourist experiences can be effective strategies in supporting the growth of halal tourism in Aceh, both in terms of policy, marketing, and improving service quality.